BUDIDAYA TANAMAN JAGUNG PADA LAHAN BERPENUTUP TANAH KACANGAN DISERTAI PEMUPUKAN NITROGEN - B. H. Tampubolon (Fakultas Pertanian, Universitas Syiah Kuala, 2003)
A field experiment has been conducted at Kebun Percobaan IPB Darmaga Bogor, with an altitude of 250 m and the soil type is latosol. The aim of experiment was to find out the growth and the yield of corn plante on land with leguminous cover crop of 2 weeks old at the time the corn seeds being planted. Statistically, randomized block design with 2 factors was used in the experiment. The first factor was the leguminous comprised of without legumes, Calopogonium caeruleum and Centrocema pubescens. The second factor namely the application of Nitrogen : 0, 60, 120, and 180 kg N/ha. The plot size was 8 m x 5 m, and three replication. In one plot, there were 5 rows of legumes. The corn was planted in 4 rows between the legumes with 25 cm distance in the row. The result of the experiment showed that the value of the parameters growth, yield and shelled corn product in the intercropping system were higher than that planted without cover crop. The highest shelled corn (3,85 ton/ha) was attained from treatment without leguminous and without Nitrogen applications. The cover crop hindered from growth of seeds, and dry weight of weeds obtained from the plot with cover crop was than that obtained from without cover crop.